The future of green finance: how digital transformation and FinTech drive sustainability - Mohammed Abdulrahman Kaid Zaid; Mohammed Farooque Khan; Abdul-Wasea Abdul-Ghani Saif Al-Mekhlafi; Ibraheem Saleh Al Koliby; Oussama Saoula; Hayat Atta Elmnan Mohammed Saeed; Reda Abdelfattah Mohammad (Discover Sustainability)
Abstract Despite the growing interest in green finance, its impact on sustainable performance remains inconclusive. This study investigates the effect of green finance on sustainable performance while exploring the moderating roles of financial technology (FinTech) adoption and digital transformation in this relationship. Using a survey of 152 employees from Saudi banks, data were analyzed using hierarchical regression with the PROCESS Macro tool. The results confirm a positive relationship between green finance and sustainable performance. In addition, FinTech adoption significantly moderates this relationship, enhancing the effectiveness of green finance. Importantly, the three-way interaction analysis reveals that digital transformation acts as a second-order moderator, as it strengthens the moderating effect of FinTech in the green finance–sustainable performance relationship. These results offer valuable insights into how digital capabilities condition the effectiveness of green finance in emerging economies. For policymakers and financial institutions, the findings highlight the importance of integrating digital tools and infrastructure to fully harness the benefits of green finance, where they suggest that the adoption of advanced financial technologies in conjunction with digital transformation can enhance sustainable performance, particularly in economies undergoing digital and environmental transitions, such as Saudi Arabia.